Comparison of efficacies of vegetable oil based and polyethylene glycol based bisacodyl suppositories in treating patients with neurogenic bowel dysfunction after spinal cord injury: A meta-analysis - Yi, Zhu; Jie, Cheng; Wenyi, Zhang; Bin, Xie; Hongzhu, Jin (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: We performed a meta-analysis to compare the efficacies of vegetable oil based bisacodyl (VOB) and polyethylene glycol based bisacodyl (PGB) suppositories in treating patients with neurogenic bowel dysfunction (NBD) after spinal cord injury (SCI). Materials and Methods: Relevant clinical studies (up to February 2014) were retrieved through the following databases: PubMed, MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials (CCTR), Chinese National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database (CBM), Wanfang, and VIP database for Chinese Technical Periodicals. Data were analyzed using the standardized weighted mean difference (SMD) and its 95% confidence interval (CI). P-values <0.05 were considered statistically significant. Results: A total of 3 studies were included in the meta-analysis. The SMD and its 95% CI were not calculated owing to unreported standard deviations in the individual studies. The average and p-values of statistical difference indicated that the total bowel care time (p<0.05), time to flatus (p<0.05), and defecation period (p<0.05) were shorter in patients treated with PGB than in patients treated with VOB. No significant difference was observed in time to clean up (p>0.05) between patients in the PGB and VOB groups. Conclusion: Based on the results, we conclude that the PGB suppository could act faster than the VOB suppository in the treatment of NBD in patients with SCI.